2018
DOI: 10.1109/toh.2018.2804391
|View full text |Cite
|
Sign up to set email alerts
|

An Experimental Setup to Test Dual-Joystick Directional Responses to Vibrotactile Stimuli

Abstract: Abstract-In this paper we investigate the influence of the location of vibrotactile stimulation in triggering the response made using two handheld joysticks. In particular, we compare performance with stimuli delivered either using tactors placed on the palm or on the back of the hand and with attractive (move toward the vibration) or repulsive prompts (move away from the vibration). The experimental set-up comprised two joysticks and two gloves, each equipped with four pager motors along the cardinal directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Experimental tests, consisting in six different tests each composed by 16 random stimuli, have been performed on 38 healthy subjects and the results have been analysed in terms of accuracy and reaction times. With respect to previously published works [28,29], the experiments here presented confirmed that a stimulation on the back of the hand could lead to better results with respect to a stimulation on the palm and that an attractive mapping gives better performance with respect to a repulsive one. Furthermore, the main overall result of this novel study is given by the differences between single and sequential stimuli (Follow me condition): it has been revealed that a slow saltatory pattern could give better results in terms of proportion of correct responses compared to the other tested conditions.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…Experimental tests, consisting in six different tests each composed by 16 random stimuli, have been performed on 38 healthy subjects and the results have been analysed in terms of accuracy and reaction times. With respect to previously published works [28,29], the experiments here presented confirmed that a stimulation on the back of the hand could lead to better results with respect to a stimulation on the palm and that an attractive mapping gives better performance with respect to a repulsive one. Furthermore, the main overall result of this novel study is given by the differences between single and sequential stimuli (Follow me condition): it has been revealed that a slow saltatory pattern could give better results in terms of proportion of correct responses compared to the other tested conditions.…”
Section: Resultssupporting
confidence: 86%
“…With respect to the results obtained in previous works [28,29], where only single stimuli have been applied to test dual-joystick directional responses, the main overall aim of this case study is to investigate whether a sequential stimulation could lead to more accurate responses with respect to a single prompt. For this purpose, six different vibrotactile training mappings have been completed by the 38 subjects involved in the experiments: -two tests stimulating the palm of the hand from the actuators placed on joysticks, with attractive (move the joystick toward the vibration) and repulsive (move the joystick in the opposite direction with respect to the vibration felt) single 200 ms vibrotactile stimuli (respectively called Attractive and Repulsive Joystick ); -two tests stimulating the back of the hand from the vibrating motors placed on gloves, with attractive and repulsive single 200 ms vibrotactile stimuli (Attractive and Repulsive Glove); -two tests stimulating the back of the hand with a sequence of three vibrotactile prompts that induce the motion along the direction indicated by the saltatory pattern.…”
Section: Vibrotactile Training Mappingsmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, we investigate whether a vibration stimulating the back of the hand is more efficient than a vibration provided by the joystick and stimulating the palm of the hand. This paper is an extended version of a preliminary work presented at IEEE World Haptics Conference 2017 [36]. It is organized as follows: firstly, we provide a detailed exposition of our methods and experimental set-up (Section 2).…”
Section: Introductionmentioning
confidence: 99%